Pride and prejudice - Austen, Jane e (Phnom Penh : Footprints International School, 2024)
Mr and Mrs Bennet have five unmarried daughters. When the amiable Mr Bingly moves into the neighbourhood, Mrs Bennet therefore feels entirely sure that he is meant for one of her girls. Her eldest Miss Bennet captures his attention, but Mr Bingley's proud friend Mr Darcy does not approve the match and takes his friend away to London. Though not before losing his own heart to the second eldest, Lizzie. With an indolent father on one side and a nervous, ignorant mother on the other, the girls soon find themselves in the middle of a disaster which throws them back in with the two gentlemen. All parties must re-think their pride and the prejudice of first impressions.
Keywords: Love -- English Literature